KESEJAHTERAAN PSIKOLOGIS DITINJAU DARI SPIRITUALITAS SISWA DI LEMBAGA PENDIDIKAN BERBASIS AGAMA PESANTREN DAN NON PESANTREN - Lisnawati Lisnawati; Ifah Afifah Dayyanah Al Rahmah (UIN Sunan Kalijaga, 2018)
This study aims to determine the relationship between spirituality with psychological well being in students of Islamic Boarding School and State Islamic High School, as well as the differences of the students psychological well being of State Islamic High School and Islamic Boarding House. The research subjects of the 3rd grade students of State Islamic High School and Islamic Boarding House, each represented by 45 students, the data collection tool used in this research is the scale of spirituality and psychological well being scale. The sampling technique used in this research is purposive sampling technique. Data analysis method used in this research is product moment technique and independent sample t test. The result of correlation analysis shows that the relation of spirituality with psychological well being in State Islamic High School has r value of 0.794 and p value of 0.000 (P <0,05) and the result of spirituality analysis with psychological well being in Islamic Boarding House has r value of 0,742 and p value 0.000 (P <0.05) thus the two results indicate a very significant positive relationship. Based on these two results can be drawn the conclusion the higher the level of spirituality, the higher the psychological well being in the students, and it can be concluded that the first hypothesis in this study, that there is a positive relationship between the spiritual and psychological well being accepted. The result of psychological well being test analysis on students at State Islamic High School and Islamic Boarding House has value of difference index (T) psychological well being in State Islamic High School students and Islamic Boarding House of 5.407 with significance level (P) of 0,000 (P <0,05) and mean on student State Islamic High School is 133,71 while in Islamic Boarding House students equal to 120,10. So the psychological condition well being subject in State Islamic High School is higher than the Islamic Boarding House. The second hypothesis is that there is a difference of psychological well being in State Islamic High School and Islamic Boarding House students accepted. Keywords: Spirituality, Psychological well being